Working toward connectedness: local and international students' perspectives on intercultural communication and friendship-forming1. Issue 7 (10th November 2022) - Willoughby-Knox, Brie; Yates, Lynda
ABSTRACT : A lack of connectedness between local and international students in the higher education context is a perennial concern that negatively impacts the student experience. This study draws on two surveys, focused on intercultural communication and friendship-forming, to examine the preconceptions and actual experiences of local and international students at the beginning and end of their first term of study. It was found that, while intercultural friendships were important to both groups at the outset, they construed these relationships in distinct ways. The local group reported positive experiences and claimed responsibility for those successes, whilst the international group was dismayed at the difficulties they had forming intercultural friendships and felt that the onus for this fell largely on them. Central to the disconnect was a lack of communication skills, which both groups reported did not improve as much as they had anticipated. Strategies for helping students improve their communication skills, foster intercultural friendships and work toward greater connectedness are then given.